2011
DOI: 10.1021/je1008087
|View full text |Cite
|
Sign up to set email alerts
|

Complex Formation, Metal Uptake, and Sorption Kinetics of a Chemically Modified Chlorosulfonated Polystyrene with Aminosalicylic Acid

Abstract: The resin (PsSO2ASA) was synthesized by the reaction of chlorosulfonated polystyrene (Ps-SO2Cl) with 4-aminosalicylic acid (ASA) and characterized by elemental analysis, SEM, EDS, and FT-IR spectral studies and thermal analysis. Its metallopolymer complexes with Co(II), Ni(II), and Cu(II) ions were examined with respect to various experimental parameters. The spectral (FT-IR, electronic, and ESR) studies confirmed that the octahedral complexes formed and the resin bonded to the metal ion through the carboxylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The complex transport behavior of liquids in polymers has been studied extensively for over 60 years and reviewed by several authors. It is now widely agreed that transport involves both a diffusion process, controlled by a concentration gradient, and a relaxation process, controlled by a time-dependent response of the polymer to a stress. As the relative contributions of these two processes change and interact, a wide range of behaviors can be encountered.…”
Section: Discussionmentioning
confidence: 99%
“…The complex transport behavior of liquids in polymers has been studied extensively for over 60 years and reviewed by several authors. It is now widely agreed that transport involves both a diffusion process, controlled by a concentration gradient, and a relaxation process, controlled by a time-dependent response of the polymer to a stress. As the relative contributions of these two processes change and interact, a wide range of behaviors can be encountered.…”
Section: Discussionmentioning
confidence: 99%
“…The negative values of enthalpy changes for three resins suggested that the adsorption processes were exothermic. (El-Dissouky, Elassar, & Bu-Olian, 2011;Zhou et al, 2011). Thus, the adsorption processes of adlay bran free phenolics for three resins could be performed at room temperature.…”
Section: Resinsmentioning
confidence: 99%
“…Table 3 and figures 6 and 7 show the thermal decomposition temperatures of modified CS and its complexes with different metals. The weight loss percentage for the CS and its metal complexes in the temperature <200 • C were due to the loss of absorbed or adsorbed water, in addition to H-bonding in the polymeric material [33]. In the case of modified CS, the maximum loss at 275.22 • C was 46.62%.…”
Section: Tga Analysismentioning
confidence: 97%